2018
DOI: 10.1037/xge0000390
|View full text |Cite
|
Sign up to set email alerts
|

Tool use changes the spatial extension of the magnetic touch illusion.

Abstract: Characterizing the brain mechanisms that allow humans to use tools to interact with the environment is a major goal in neuroscience. It has been proposed that handheld tools are incorporated into the multisensory representation of the body and its surrounding (peripersonal) space, underlying our remarkable tool use ability. One single-cell recording study in tool-using monkeys provided qualitative support for this hypothesis, and the results from a vast number of human studies employing different experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…More directly, Guterstam and colleagues have reported that when brushstrokes are applied in mid-air near participants hands concurrently with touch on their real hand, subjects report feeling a “magnetic touch illusion” 54 . Further, in line with PPS encoding, this illusion shows a non-linear decay at approximately 40 cm from the hand 54 , and this area of space increases following tool-use 55 . In turn, Guterstam and colleagues suggest that the “magnetic touch illusion” is a perceptual correlate of visuo-tactile integration in the PPS 54 , and taken together, these results imply that the PPS allows for the inference of putative touch by nearby objects.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…More directly, Guterstam and colleagues have reported that when brushstrokes are applied in mid-air near participants hands concurrently with touch on their real hand, subjects report feeling a “magnetic touch illusion” 54 . Further, in line with PPS encoding, this illusion shows a non-linear decay at approximately 40 cm from the hand 54 , and this area of space increases following tool-use 55 . In turn, Guterstam and colleagues suggest that the “magnetic touch illusion” is a perceptual correlate of visuo-tactile integration in the PPS 54 , and taken together, these results imply that the PPS allows for the inference of putative touch by nearby objects.…”
Section: Introductionmentioning
confidence: 59%
“…Such probability changes the way multisensory signals are integrated/segregated and, because of this influence, the impact of PPS on perception may be indexed by using a task that measures the attraction of signals toward the expected mapping with different incongruences between multisensory signals (much as in Guterstam et al . 54 , 55 with the “magnetic touch illusion”). We can estimate the shape of the a priori visuo-proprioceptive coupling by asking participants to indicate where they perceive their finger (e.g., their left index) as well as visual cues in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…More directly related to bodily self‐consciousness, a number of groups have shown that tactile stimulation of the body is not necessary to induce bodily illusions, but solely implying tactile sensation emanating from the PPS may elicit changes in bodily representation . Furthermore, these tactile predictions may have a phenomenological correlate . Guterstam and colleagues applied brushstrokes in mid‐air at some distance above a rubber hand—without touching it—and in synchrony applied brushstrokes to the participant's hidden hand.…”
Section: Bodily Self‐consciousnessmentioning
confidence: 99%
“…However, haptic illusions such as these (see also Guterstam et al, 2011Guterstam et al, , 2018, while striking and unusual, lack the genuinely "impossible" character of the present phenomenon. In other words, sprouting a new nose or extending one's arm past its breaking point are certainly biologically implausible experiences; but the present phenomenon is not merely strange or unusual-it is physically or even conceptually incoherent.…”
Section: Discussionmentioning
confidence: 58%